An agent-‐based simulation system to support an approach to brand perception measurement (2012)
Abstract. A theoretical approach for measuring the brand perception of a single organisation in a heterogeneous group of persons of arbitrary size and supported by an intelligent agent based system is presented. The system is based on the interaction of two types of agents: on one side, groups of acquiescent agents modelled after a given brand’s potential customers and aware of environmental disturbances produced by an organisation in form of influencing agents on the other. The relation is based on the perspective that a person may define an organisational value by returning her own perception to the environment, an organizational value that in some way has been interiorised. Once her perspective finds a way to the environment again, it gains new life and is able to influence other people. The aim of the mentioned system is to evaluate the effect of the discriminated marketing investment made to expose different values of the organisation. Management aspires people to interiorise these values and to return them untouched to their peers to interiorise them later too. By making the investment aspect clear, the management may become aware of which resources are being well spent and which ones need a to be redirected to really reach their desired target in accordance to the people’s response, an aspect clearly presented by the simulation process. So, differences among the customer groups were modelled by determining their members’ sensibility towards influences and the capacity to produce an active response to such stimuli. An active response in terms of the system was modelled in two ways: (i) is to return the influences back to the environment or (ii) to terminate them abruptly. Influencing agents are also gathered by common given objectives to form groups but maintain a certain degree of independence by being more or less prone to survive in the environment. This last feature was modelled after the investment effort made by an organisation towards the penetration of own values to be perceived by the public.